PENGARUH KEGIATAN POSYANDU AYAH TERHADAP PENCAPAIAN SKDN DI POSYANDU DESA PULO GEBANG DAN POSYANDU DESA GUBUS BANARAN WILAYAH KERJA PUSKESMAS TEMBELANG KABUPATEN JOMBANG: Influence of Posyandu Ayah Activities on Achievement of SDKN in Posyandu Pulo Gebang Village and Posyandu Banaran Village in Working Area of Puskesmas Tembelang, Jombang District - Mudhawaroh Mudhawaroh; Septi Fitrah Ningtyas; Niken Grah Prihartanti (LPPM - STIKES Pemkab Jombang, 2020)
Introduction: Posyandu is one form of Community-Based Health Efforts (UKBM) which is managed and organized from, by, for, and together with the community in organizing health development, in order to empower the community and provide facilities to the public in obtaining basic health services to accelerate the decline in numbers maternal and infant deaths. In addition, posyandu is a form of community participation that truly carries enormous significance for the health and welfare of the community. Posyandu success can be seen from the achievement of SKDN. The purpose of this research is to analyze the influence of father's Posyandu activities on the achievement of SKDN. Method: This study used an observational analytic method with a cross sectional study design. The population in this study is the population in this study are all participants in Posyandu activities, the sampling technique used in this study is simple random sampling. A sample of 50 people in both groups. Data analysis was performed by univariate and bivariate, statistical testing using the Mann Whitney Test with a confidence level of 95% (? = 0.05). Results: Almost all toddlers in the father's posyandu group experienced an increase in July - September by 44 (88%) and in the control group the majority rose by 34 (68%). Respondent participation (D / S) with a value> 80% was found in the case group, while the increase in body weight in the last 3 months with a value> 80% was found in the case group. p <?, where the value is 0.047 <0, 05 so that it can be concluded that there is an influence of the father's Posyandu activity on the achievement of SKDN. Discussion: With the presence of the father's posyandu and toddlers' posyandu, it can increase public awareness about the importance of toddler health, by participating will also increase the child's weight. The simplest indicator in a posyandu is